X-2(4x+9)=8-7x

Simple and best practice solution for X-2(4x+9)=8-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-2(4x+9)=8-7x equation:


Simplifying
X + -2(4x + 9) = 8 + -7x

Reorder the terms:
X + -2(9 + 4x) = 8 + -7x
X + (9 * -2 + 4x * -2) = 8 + -7x
X + (-18 + -8x) = 8 + -7x

Reorder the terms:
-18 + X + -8x = 8 + -7x

Solving
-18 + X + -8x = 8 + -7x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + X + 18 + -8x = 8 + 18 + -7x

Reorder the terms:
-18 + 18 + X + -8x = 8 + 18 + -7x

Combine like terms: -18 + 18 = 0
0 + X + -8x = 8 + 18 + -7x
X + -8x = 8 + 18 + -7x

Combine like terms: 8 + 18 = 26
X + -8x = 26 + -7x

Add '8x' to each side of the equation.
X + -8x + 8x = 26 + -7x + 8x

Combine like terms: -8x + 8x = 0
X + 0 = 26 + -7x + 8x
X = 26 + -7x + 8x

Combine like terms: -7x + 8x = 1x
X = 26 + 1x

Simplifying
X = 26 + 1x

See similar equations:

| x+53=5x+17 | | 30(x^2-3x)=120 | | 4x+9=12-4x-5 | | bn=(-2)n-1 | | F(2)=(x-4)2 | | S-5=79 | | v^2-v-6=6 | | 10n^2-20n=12 | | x^2+y^2+18x+8y+97=4 | | 3-3*2+2= | | -11=-5+2v | | 2x^2-17+21=0 | | 4n^2+16n-54=0 | | 6x+9x=3+8x+4 | | -3(x+4)3+3=27 | | Y=-3(-2)+b | | 6n^2=-12n+11 | | -a^6+5=2 | | a-(-6)=10 | | 7x+3=5x-6 | | 8a^2=16a+64 | | 3x(x-1)+2+(x-1)=0 | | lg(2x+1)-lg(x-1)=0.5 | | 3x*6x*2x^3= | | 50=8-2y | | 2x+9+3x+8+5y-2y= | | x^2+4x-8=4 | | 1.5z+1.5=5.4 | | -2(17x-4)+7(5x-3)-5=3-4 | | 3w=5w-20 | | 4x-9=3x+3-5x | | 2(x+1)3-3=13 |

Equations solver categories